Analisis dan karakterisasi genteng polimer berbahan baku ban dalam bekas, pasir dan aspal dengan perekat polipropilenae - mega puspita (Saintia Fisika, 2013)
Studies of polymer roof have been made with using tube rubber, polypropylene, sand, Asphalt and epoxy. Studies have been done to know the best combination of sand and tube rubber as free variable with composition of variations to 30:20gr, 32,5:17,5 gr, 35:15 gr, 37,5:12,5 gr, 40:10 gr, 42,5:7,5 gr, 45:5 gr, 47,5:2,5 gr. Then, constant variable has asphalt to 5 gr, poliypropilene 30 gr and epoxy 15 gr as glue in combination. tube-rubber waste melted (with extruder) and then it mixed with asphalt, sand, polypropylene, epoxy and catalyst. Then it was grinded in internal mixer for 1 hour at temperature of 150 0C. Then it was pressed with using Hot Compressor for 20 minutes with pressure 38 atm (38,5 x 105 Pa). The properties of polymer roof that analyzed to test physical properties such as water absorption and porosity, mechanical properties including impact test and bending strength test and thermal properties including Differential thermal Analysis test .The result of research show that the best combination based on test is the combination from sand and tube rubber with ratio (55:10) and additional 5 gr of asphalt as binding,30 gr of polypropylene with epoxy 14% and catalyst 1% Key words : tube rubber, polypropilene, Polymer Roof, Sand and Asphalt